2012
DOI: 10.1002/jbmr.1621
|View full text |Cite
|
Sign up to set email alerts
|

miR-93/Sp7 function loop mediates osteoblast mineralization

Abstract: microRNAs (miRNAs) play pivotal roles in osteoblast differentiation. However, the mechanisms of miRNAs regulating osteoblast mineralization still need further investigation. Here, we performed miRNA profiling and identified that miR-93 was the most significantly downregulated miRNA during osteoblast mineralization. Overexpression of miR-93 in cultured primary mouse osteoblasts attenuated osteoblast mineralization. Expression of the Sp7 transcription factor 7 (Sp7, Osterix), a zinc finger transcription factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 37 publications
1
61
0
2
Order By: Relevance
“…miR-125b-5p, miR-30e-3p and miR-204-5p), whereas several of them (e.g. miR-93-5p and miR-203-3p) had been reported to negatively regulate osteogenesis (Table S3) (Kennell et al, 2008;Hamam et al, 2014;Yang et al, 2012;. Eguchi et al also analyzed the miRNAs in adipocytes derived from EVs and detected several adipogenic miRNAs (including miR-148a-3p, miR-181a-5p, miR30a-5p, miR-125b-5p) (Eguchi et al, 2016), which is consistent with our results (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…miR-125b-5p, miR-30e-3p and miR-204-5p), whereas several of them (e.g. miR-93-5p and miR-203-3p) had been reported to negatively regulate osteogenesis (Table S3) (Kennell et al, 2008;Hamam et al, 2014;Yang et al, 2012;. Eguchi et al also analyzed the miRNAs in adipocytes derived from EVs and detected several adipogenic miRNAs (including miR-148a-3p, miR-181a-5p, miR30a-5p, miR-125b-5p) (Eguchi et al, 2016), which is consistent with our results (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play a key role in various biological processes including osteoblast differentiation and mineralization. (29)(30)(31) Osteoclastogenesis is also regulated by miRNAs. In the present study, we performed microarray assays and found miR-148a dramatically upregulated during osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…В определенной степени, остерикс (OSX) -транс-крипционный фактор, необходимый для формирования костной ткани, находится под контролем мкРНК, образуя уникальную ауторегуляторную петлю обратной связи с мкРНК93. мкРНК93 ингибирует минерализацию, воз-действуя на OSX [47]. Wnt-сигнальный путь также нахо-дится под контролем определенных мкРНК.…”
Section: роль мкрнк в костном ремоделированииunclassified
“…Таргетная молекула Источник мкРНК, стимулирующие дифференцировку остеобластов мкРНК27, микроРНК142-3p APC [51,52] мкРНК29a Дкк1, KREMEN2, сФРЗ2, SPARC [48,54] мкРНК29b COL1A1, COL5A3, COL4A2, HDAC4, ТФРβ3, ACVR2A, CTNNBIP1, DUSP2 [55] мкРНК218 SOST, Дкк2, сФРЗ2 [49] мкРНК335-5p Дкк1 [50] мкРНК, блокирующие дифференцировку остеобластов мкРНК23a RUNX2, SATB2 [37,43,44] мкРНК30a-d RUNX2, SMAD1 [38,43,44] мкРНК34c, мкРНК133a, мкРНК137, мкРНК204, мкРНК205, мкРНК211, мкРНК217, мкРНК335, мкРНК338, мкРНК433, мкРНК3077-5p RUNX2 [39][40][41][42][43][44]53] мкРНК93 OSX [47] мкРНК135a RUNX2, SMAD5 [39,43,44] мкРНК155 SOCS1 [56] Примечание. APC -аденоматозная полипозная палочка; Дкк1 и 2 -Диккопф 1 и 2; KREMEN2 -кринглсодержащий трансмембран-ный белок; сФРЗ2 -секреторный белок, связанный с фризельдом 2; SPARC -секретируемый белок, кислый, богатый цистеином (остеонектин); COL1A1 -коллаген, тип I, α 1; COL5A3 -коллаген, тип V, α 3; COL4A2 -коллаген, тип IV, α 2; HDAC4 -гистонде-ацетилаза 4; ТФРβ 3 -трансформирующий фактор роста β 3 ; ACVR2A -рецептор типа 2А к активину А; CTNNBIP1 -белок, взаимо-действующий с β-катенином, 1; DUSP2 -фосфатаза двойной специфичности, тип 2; SOST -склеростин; RUNX2 -фактор транс-крипции 2, содержащий домен Runt; SATB2 -ДНК-связывающий белок; SMAD1 и 5 -семейство SMAD тип 1 и 5; OSX -остерикс; SOCS1 -супрессор цитокиновых сигналов 1.…”
Section: мкрнкunclassified